Pemberdayaan Masyarakat Desa Mekar Sari Melalui Pemanfaatan Sampah Plastik Menjadi Paving Block - Suroyo, Suroyo; Maulana, Fajar; Ilham, Vicky Dixondra; Ramelda, Meliyani; Verawati, Ketut; Purba, Niki Dwi Nastiti; Sirait, Shelvia Sharon; Sihombing, Valencia Helena Andata; Safitri, Salsha; Fitnes, Fitnes; Salosa, Angga Fatrias Myloudri (Yayasan Daarul Huda Kruengmane, 2024)
The issue of plastic waste in Mekar Sari village has become an increasingly serious environmental concern, as the amount of plastic waste continues to rise alongside changes in lifestyle and consumption patterns of the community. Poorly managed plastic waste can pollute the environment and pose a threat to human health. Therefore, innovative solutions are needed through a program that utilizes plastic waste to create paving blocks. This program aims to reduce the negative impact of plastic waste on the environment and to enhance the skills and knowledge of the community in managing plastic waste, thereby increasing their economic value and well-being. The methods used in this service include observation, socialization, and training in the production of paving blocks from plastic waste for the local community. The results of this program show that the community of Mekar Sari Village has successfully utilized plastic waste, which was previously just garbage, into economically valuable products in the form of paving blocks. In addition, the community has become more aware of the importance of protecting the environment, as seen in their increased participation in various cleanliness and environmental preservation programs.